2018
DOI: 10.1111/wej.12348
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance of constructed wetland for water quality management of a Southern Mediterranean river

Abstract: Most of Southern Mediterranean water courses suffer from numerous types of pollution. This study presents a comprehensive performance assessment of a pilot CW system for removing various contaminants from the Litani River, Lebanon. The physico‐chemical, pathogens and trace metal parameters were analyzed for river water as well as for the wetland effluent. Results revealed that the average removal efficiencies were 87.01% for COD, 64.99% for BOD5, 86.18% for TSS, 43.11% for NO3N, 34.82% for NH4N, 55.07% for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Hayward, Jackson, Yost, Truelstrup Hansen, and Jamieson (2018) examined the seasonal impact on the performance of two Arctic tundra wetlands (Sanikiluaq and Naujaat) treating municipal wastewater and reported that E. coli reduction was higher in summer season (5 log reduction) when compared with spring season (0.04 log reduction). Abi Saab et al (2018) examined the efficiency of a CW on the removal of pathogens and showed that the highest removal of TC (99.98% removal), FC (99.84% removal), E. coli (96.51% removal), and Salmonella (100% removal) was observed in the months of April and May.…”
Section: Wetlands For Pathogens and Virus Removalmentioning
confidence: 99%
“…Hayward, Jackson, Yost, Truelstrup Hansen, and Jamieson (2018) examined the seasonal impact on the performance of two Arctic tundra wetlands (Sanikiluaq and Naujaat) treating municipal wastewater and reported that E. coli reduction was higher in summer season (5 log reduction) when compared with spring season (0.04 log reduction). Abi Saab et al (2018) examined the efficiency of a CW on the removal of pathogens and showed that the highest removal of TC (99.98% removal), FC (99.84% removal), E. coli (96.51% removal), and Salmonella (100% removal) was observed in the months of April and May.…”
Section: Wetlands For Pathogens and Virus Removalmentioning
confidence: 99%
“…A constructed wetland was established in 2013 by Litani River Basin Management Support (USAID/LRBMS) and the Litani River Authority in the Upper Litani River, Kherbit Kanafar in the southern plains of the Bekaa Valley [26,48,49]. Directly adjacent to the Litani River, this wetland is covering an area of 2.6 ha located within the south Bekaa irrigation scheme.…”
Section: Pilot Constructed Wetland In Kherbit Kanafarmentioning
confidence: 99%
“…Similarly, higher improvement levels with dissolved oxygen (DO) and biochemical oxygen demand (BOD) both of which witnessing changes by around 25% and 66%, respectively. Abi Saab et al [49] revealed an increase in the removal efficiency of most pollutants (about 80 %) emphasizing the importance of the wetland plants in the removal of pollutants including nutrients, pathogens and trace elements.…”
Section: Pilot Constructed Wetland In Kherbit Kanafarmentioning
confidence: 99%
“…The rapid development of society and intensification in agriculture has improved living standards but also caused various water-related issues, especially pollution and the degradation of wetland ecosystems [1][2][3]. Moreover, conditions are worsening in developing economies due to the integrated effect of anthropogenic activities, escalating demand of resources, and population explosion [4].…”
Section: Introductionmentioning
confidence: 99%